A heat exchanger network design for an ammonium plant: A supertarget application - Dogru, E; Ozkan, S; Bolat, E (HUNGARIAN CHEMICAL SOC, 1999)
In this study, a heat exchanger network was designed for an ammonium plant namely IGSAS (Istanbul Gubre Sanayii A.S.), in Izmit, Turkiye and for an optimum design DeltaT(min) restriction was changed and its effects on the heat exchanger area, the energy cost and the total cost of the plant were examined. SuperTarget software from Linhoff March Ltd. U.K., was used to analyse the energy requirements of the process and to determine the optimum DeltaT(min) value. From the calculations, the optimum DeltaT(min) value was found as 5 degreesC and the total heat exchanger area was found below than the area of the existing plant.
Keywords: heat integration; heat exchanger networks(HEN's); pinch; cost; Engineering; Environmental Sciences & Ecology